ANALISIS DIKABULKANNYA PERMOHONAN PENINJAUAN KEMBALI SETELAH PELAKSANAAN PUTUSAN SENGKETA GADAI TANAH ULAYAT - Aulia Ade Putra (STIH Putri Maharaja, 2019)
The settlement of agricultural land plot disputes over communal ulayat often culminates in the settlement in the realm of the Court. The judge's ruling is based on Law Number 56 Prp of 1960 and there are decisions based on Minangkabau Traditional Law. The problem was how the consideration of the panel of judges on the settlement of agricultural land disputes over ulayat of the people in the decision of Review of number 394 PK/PD/2011 and How the position of the land buyer in the settlement of agricultural land disputes disputes over ulayat people after the release of judgment review number 394 PK/PDT/2011. The method used to solve the problem was normative juridical, meaning that by using the approach of legislation and relevant theory will illustrate the legal certainty relating to the problems that have been formulated. The result of the research which was derived from the problem formulation was obtained the result, the settlement of agricultural land disputes over the ulayat of the people in the court should be based on the National Legislation and the Minangkabau Adat Law provisions, the two legal bases are contradicted and in the decision of Review Number 394 PK/PDT/2011, the Panel of Judges of Judicial Review did not base the judgment of the Review on the National Law and Minangkabau Customary Law and the possession of the object was submitted to the purchaser of the object of such pledge. The judge's opinion on this Review was false, unfounded and not fair because it was inconsistent with the National Law and Minangkabau Law.